Amyloid‐associated increases in longitudinal report of subjective cognitive complaints. Issue 1 (5th September 2018) - Amariglio, Rebecca E.; Buckley, Rachel F.; Mormino, Elizabeth C.; Marshall, Gad A.; Johnson, Keith A.; Rentz, Dorene M.; Sperling, Reisa A.
Abstract: Introduction: To investigate whether baseline subjective cognitive complaints (SCCs) predict longitudinal decline on neuropsychological testing and whether SCC increases longitudinally, in the setting of high levels of amyloid burden. Methods: Two hundred seventy‐nine clinically normal older participants (mean age = 73.7 ± 6.1 years) from the Harvard Aging Brain Study, a cohort of community‐dwelling individuals, were followed longitudinally (4.27 ± 1.35 years) with annual subjective memory questionnaires and neuropsychological assessment. 11 C Pittsburgh compound‐B positron emission tomography was used to measure cortical amyloid and to classify status (Aβ+/Aβ−) at baseline. Results: Higher baseline SCC predicted more rapid cognitive decline on neuropsychological measures among those with elevated amyloid (t = −2.18, P  < .0001). In addition, longitudinal report of SCC significantly increased over time, with SCC progression most pronounced among Aβ+ individuals (t = 2.24, P  = .0005). Discussion: SCC may inform risk for future cognitive decline and track progression of self‐perceived decline, particularly in those along the AD trajectory, providing potentially important indicators of clinical meaningfulness in AD prevention trials.